A survey of root knot nematodes and resistance to Meloidogyne incognita in sweet potato varieties from Kenyan fields. (February 2017) - Karuri, Hannah W.; Olago, Daniel; Neilson, Roy; Mararo, Enock; Villinger, Jandouwe
Abstract: The root knot nematode, Meloidogyne is one of the most economically damaging plant parasitic nematode groups, and are widely distributed in Kenyan agro-ecosystems. The aim of this study was to determine the diversity of Meloidogyne species in Kenyan sweet potato fields and identify sweet potato varieties that exhibit resistance to M . incognita . Meloidogyne species were collected from Nyanza, Western, Eastern and Central Provinces of Kenya. Mitochondrial DNA was used to differentiate Meloidogyne species. The most common species in all sampled regions was M . incognita . Meloidogyne hapla was recorded for the first time in Kenyan sweet potato growing areas (Mosocho, Matayos, Teso South, Manyatta, and Nzaui sub-counties), while M . enterolobii was observed in Kiharu, Matayos and Mosocho sub-counties and a novel Meloidogyne sp. was identified in Kiharu sub-county. Seventy-two sweet potato varieties collected from both agricultural fields and research stations in Kenya were evaluated for resistance to M . incognita under greenhouse conditions in two separate trials. Known susceptible (Beauregard) and resistant (Tanzania) sweet potato varieties were included as controls. Responses of sweet potato varieties to M . incognita infection was assessed by the number of eggs present and level of galling on a scale of 1–5, where 0 = 0 galls and 5 ≥ 100 galls. The reproduction index (RI) was used to classify the varieties as resistant or susceptible. There was a significant difference (P < 0.001) in the number of eggs, GI and RI among the varieties tested. Forty nine sweet potato varieties were considered very resistant and may be used in breeding programs to incorporate resistance against M . incognita into commercial cultivars of sweet potato or to use them in crop rotation programmes for management of RKN. The results on Meloidogyne species diversity in Kenyan sweet potato fields will also be useful in nematode management programs. Highlights: Meloidogyne incognita is the most prevalent species in Kenyan sweet potato fields. Other Meloidogyne species in Kenyan sweet potato fields are M . hapla and M . enterolobii. Forty nine out of 72 sweet potato varieties that were tested were very resistant to M . incognita .